2011
DOI: 10.1371/journal.pone.0020368
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Parieto-Premotor Network Is Associated with Vivid Motor Imagery—A Parametric fMRI Study

Abstract: The present study examined the neural basis of vivid motor imagery with parametrical functional magnetic resonance imaging. 22 participants performed motor imagery (MI) of six different right-hand movements that differed in terms of pointing accuracy needs and object involvement, i.e., either none, two big or two small squares had to be pointed at in alternation either with or without an object grasped with the fingers. After each imagery trial, they rated the perceived vividness of motor imagery on a 7-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 34 publications
2
66
0
Order By: Relevance
“…Patients, on the other hand, performed overt execution (each patient was able to produce an overt wrist movement at least once, see Table 2 and Supplementary Table 2) only after the other conditions had been acquired, so that the motor image was probably based on movements longer ago, maybe even from pre-stroke times. This may have resulted in a less vivid motor image, which may have resulted in lower activation levels (Lorey et al, 2011). However, it is noteworthy that Imagery was nevertheless the covert movement mode which resembled attempted execution best.…”
Section: Comparison Of Movement Modesmentioning
confidence: 98%
“…Patients, on the other hand, performed overt execution (each patient was able to produce an overt wrist movement at least once, see Table 2 and Supplementary Table 2) only after the other conditions had been acquired, so that the motor image was probably based on movements longer ago, maybe even from pre-stroke times. This may have resulted in a less vivid motor image, which may have resulted in lower activation levels (Lorey et al, 2011). However, it is noteworthy that Imagery was nevertheless the covert movement mode which resembled attempted execution best.…”
Section: Comparison Of Movement Modesmentioning
confidence: 98%
“…Lorey et al [30] studied the relationship between activation of the cerebral cortex during MI and the vividness of MI by fMRI. The primary motor cortex, premotor area, primary somatosensory area, inferior parietal lobe and superior parietal lobe, putamen, and cerebellum showed activation during MI.…”
Section: The Changes Of Spinal Motor Neuron Excitability During MI Unmentioning
confidence: 99%
“…Imagery can be divided into two main types: first-person (muscular sensory) imagery and third-person (visual) imagery. Studies have shown that the dorsolateral prefrontal cortex, inferior frontal gyrus, premotor cortex, primary somatosensory cortex, and inferior parietal lobule are activated during first-person imagery [6,37,38]. Moreover, the left inferior parietal lobule is activated more during first-person imagery than during third-person imagery [39].…”
Section: Imagerymentioning
confidence: 99%